Efeitos do cis-JASMONE na indução de compostos fenólicos em genótipos de soja, inoculados ou não com Meloidogyne javanica - Janegitz, Tatiani (2012)
The induction of defense compounds by cis-jasmone and damage Meloidogyne javanica in soybean genotypes resistant and susceptible to root-knot nematodes was analyzed. Seedlings of BRS 133 (susceptible) and PI 595099 (resistant) were treated with foliar spraying or soil drench and inoculated with the nematode. Root extracts were analyzed by high performance liquid chromatography (HPLC) to phenolic compounds identification and PAL activity. Reproduction of nematode was determined by the reproduction factor (FR). The foliar spraying with cis-jasmone systemically induced PAL activity after 120h of application, and the synthesis of daidzein, genistein and coumestrol were observed after 144h; and this induction was higher in the resistant genotype. Effects of foliar spraying with cis-jasmone plus inoculation were observed by increasing the PAL activity after 72h inoculation and induce phytoalexin coumestrol after 144h. In plants treated with soil drench, the PAL activity and of isoflavone concentrations were higher in the control and susceptible genotype, but when treated with soil drench plus inoculation, were higher in the resistant genotype. These results suggest that induction of systemic form of phytoalexin coumestrol, in the roots of soybeans, for cis-jasmone well as in response to nematodes parasites may be related to soybean resistance to M. javanica.